Aspectele de drept penal ale provocării luării de mită sau a dării de mită [Articol] - Brînza, Cristian (CEP USM, 2020)
Combaterea fenomenului infracțional este inadmisibilă prin recurgerea la mijloace ilegale și imorale. Pornind de la această premisă, autorul își propune să stabilească conținutul noțiunii-cadru „provocarea unei fapte prevăzute de legea penală” și al noțiunii subsecvente „provocarea luării de mită sau a dării de mită”. De asemenea, scopul studiului de față constă în examinarea din perspectiva de lege lata și de lege ferenda a problemei provocării unei fapte prevăzute de legea penală, inclusiv problema provocării luării de mită sau a dării de mită. Se argumentează că provocarea unei fapte prevăzute de legea penală este o instituție de sine stătătoare, diferită de instituția participației. Este formulată definiția noțiunii „provocarea unei fapte prevăzute de legea penală”: fapta provocatorului de inițiere a săvârșirii infracțiunii ce urmează a fi imputată persoanei provocate care, înainte de contactul cu provocatorul, nu fusese predispusă să comită acea infracțiune, cu condiția că persoana provocată nu conștientizează că săvârșirea infracțiunii a fost inițiată de către provocator pentru a crea o aparență, o falsă reprezentare cu privire la săvârșirea infracțiunii de către persoana provocată, și pentru a-i prejudicia prin aceasta interesele. Este propusă completarea Capitolului III din Partea generală a Codului penal cu noi prevederi privind provocarea unei fapte prevăzute de legea penală, privită drept cauză care înlătură caracterul penal al faptei. De asemenea, este recomandată completarea Capitolului XIV din Partea specială a Codului penal cu un articol în care să fie prevăzută răspunderea pentru provocarea unei fapte prevăzute de legea penală.

It is inadmissible to resort to illegal and immoral methods in order to combat crime. Starting from this premise, this article made significant strides in establishing the content of the main collocation of “provoking the comission of an act provided by the criminal law” and the content of the subsequent collocation of “challenging the act of receiving or giving bribes”. Also, this study successfully examined both these situations from the perspective of de lege lata and de lege ferenda. Accordingly, it is argued that provoking the comission of an act provided by the criminal law is an institution of its own, different from the institution of participation. To consolidate this idea, there was formulated the definition of the collocation of “provoking the comission of an act provided by the criminal law”, namely: it is the act of initiation by the provocateur towards the commission of a crime that will be imputed to the challenged person who, before getting in contact with the provocateur, was not predisposed to commit the crime in question, provided that the challenged person was not aware of the fact that the provocateur initiated the commission of the crime only to create an appearance, a misrepresentation, looking to put the entire blame on the provoked person, and by that affecting his or her interests. In this regard, there was recommended to supplement Chapter III of the General Part of the Penal Code with new provisions on the circumstance of provoking the comission of an act provided by the criminal law, accounted as a motive that negates the criminal character of the act. Also, there was recommended to supplement Chapter XIV of the Special Part of the Penal Code with an article that would apply criminal liability for provoking the comission of an act provided by the criminal law.
THE CRIMINAL LAW CONNOTATIONS WITH REGARD TO CHALLENGING THE ACT OF RECEIVING OR GIVING A BRIBE
Keywords: provocator; luare de mită; dare de mită; provocateur; receiving a bribe; giving a bribe